Assessment of propionic acid adsorption performance on the phase transformation of calcium sulfate hemihydrate to dihydrate - SAYAN, PERVİZ; POLAT, SEVGİ (TAYLOR & FRANCIS INC, 2018)
The adsorption of propionic acid during the transformation process of calcium sulfate hemihydrate to calcium sulfate dihydrate was studied in a batch-type crystallizer with respect to contact time, additive concentration and temperature in pure media, and in the presence of propionic acid used as an additive. The adsorbent was characterized by X-ray diffraction, scanning electron microscopy and thermogravimetric analysis combined with a Fourier-transform infrared spectrometer and a mass spectrometer. The adsorption characteristics were also investigated by means of evaluating the isotherm, kinetic and thermodynamic properties. The results of this investigation showed that propionic acid can serve as a good accelerator for the transformation process from calcium sulfate hemihydrate to dihydrate.
Keywords: Calcium sulfate hemihydrate; phase transformation; adsorption; propionic acid; TGA; FTIR; MS; DRUG RESIDUE; RED-DYE; KINETICS; GYPSUM; REMOVAL; EQUILIBRIUM; WATER; THERMODYNAMICS; PRECIPITATION; ADDITIVES